The Multiple Mitotic Roles of the ASPM Orthologous Proteins: Insight into the Etiology of ASPM-Dependent Microcephaly - Razuvaeva, Alyona V.; Graziadio, Lucia; Palumbo, Valeria; Pavlova, Gera A.; Popova, Julia V.; Pindyurin, Alexey V.; Bonaccorsi, Silvia; Somma, Maria Patrizia; Gatti, Maurizio (Cells (Basel, Switzerland), 2023)
The Drosophila abnormal spindle (asp) gene was discovered about 40 years ago and shown to be required for both mitotic and meiotic cell division. Subsequent studies showed that asp is highly conserved and that mutations in its human ortholog ASPM (Abnormal Spindle-like Microcephaly-associated; or MCPH5) are the most common cause of autosomal recessive primary microcephaly. This finding greatly stimulated research on ASPM and its fly and mouse (Aspm) orthologs. The three Asp orthologous proteins bind the microtubules (MTs) minus ends during cell division and also function in interphase nuclei. Investigations on different cell types showed that Asp/Aspm/ASPM depletion disrupts one or more of the following mitotic processes: aster formation, spindle pole focusing, centrosome-spindle coupling, spindle orientation, metaphase-to-anaphase progression, chromosome segregation, and cytokinesis. In addition, ASPM physically interacts with components of the DNA repair and replication machineries and is required for the maintenance of chromosomal DNA stability. We propose the working hypothesis that the asp/Aspm/ASPM genes play the same conserved functions in Drosophila, mouse, and human cells. Human microcephaly is a genetically heterogeneous disorder caused by mutations in 30 different genes that play a variety of functions required for cell division and chromosomal DNA integrity. Our hypothesis postulates that ASPM recapitulates the functions of most human microcephaly genes and provides a justification for why ASPM is the most frequently mutated gene in autosomal recessive primary microcephaly.